Contemporary Trends and Challenges in Tourism Studies: An Academic Inquiry (Journal of Science-Innovative Research in Uzbekistan, 2024)
Tourism, a multifaceted and dynamic phenomenon, holds significant importance in the global socio-economic landscape. This article provides an in-depth examination of contemporary trends and challenges within the field of tourism studies. Drawing on diverse academic perspectives, it explores the evolving nature of tourist behavior, the impact of technology, and the sustainability imperative in the context of modern tourism